2020
DOI: 10.1080/1046560x.2020.1805200
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Secondary Science Teachers’ Implementation of an NGSS Practice: Using Mathematics and Computational Thinking

Abstract: We investigated six preservice secondary science teachers' implementation of reform-based science, in particular, their teaching of the Next Generation Science Standards' (NGSS) science and engineering practice of using mathematics and computational thinking. A modified version of the Task Analysis Guide in Science served as our conceptual framework: It assesses both the integration of practices and content (i.e., the kind of thinking required), and the cognitive demand of tasks (i.e., the level of thinking re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the ratio of BAX to BCL2 could be used to predict the behavior of the cells in the apoptotic system 74 . The probiotic supernatant degrades the integrity of chromatin within the nucleus by increasing reactive oxygen species and lipid peroxidation, as well as decreasing mitochondrial membrane potential, increasing caspase-3 activity, and decreasing BCL2 anti-apoptotic activity 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ratio of BAX to BCL2 could be used to predict the behavior of the cells in the apoptotic system 74 . The probiotic supernatant degrades the integrity of chromatin within the nucleus by increasing reactive oxygen species and lipid peroxidation, as well as decreasing mitochondrial membrane potential, increasing caspase-3 activity, and decreasing BCL2 anti-apoptotic activity 75 .…”
Section: Discussionmentioning
confidence: 99%
“…In a rare study of the implementation of mathematical and computational thinking in K-12 science classrooms, Aminger et al (2021) found that teachers were able to improve students' understanding of scientific phenomena only when engaged in high cognitive demand mathematical tasks, such as mathematical modeling. Modeling uses mathematical equations to represent scientific phenomena and communicate scientific ideas (e.g., Bialek & Botstein, 2004;Brush, 2015;Lazenby & Becker, 2019).…”
Section: The Case Of Mathematicsmentioning
confidence: 99%
“…Critical to integrated STEM education, however, is that these tools should not be limited to data collection devices; rather, they should encourage deeper student engagement with science content (Bull & Bell, 2008). Moving beyond basic data practices, technology practices in STEM education can be elevated to incorporate simulation and modeling practices which have been shown to improve students' conceptual science understanding (Aminger et al, 2021).…”
Section: The Case Of Technologymentioning
confidence: 99%
“…It has also been reported that compounds of cyanidin-3-O-galactoside, eriodectiol-7-O-glucoside, and epicatechin are present in pistachio hull seem to be the cause of its antioxidant capacity 29 . The most prevalent phenols in the green pistachio hull were catechins, gallic acid, rutin, and eriodictyol-7-O-glucoside 34 , 48 . The flavan-3-ols (catechins) and flavonols are in large amounts in the pistachio hull 45 .…”
Section: Discussionmentioning
confidence: 99%